Endoscopic Full Thickness Resection: A Systematic Review - Pal, Partha; Ramchandani, Mohan; Inavolu, Pradev; Reddy, Duvvuru Nageshwar; Tandan, Manu (Journal of Digestive Endoscopy, 2022)
Background Endoscopic full thickness resection (EFTR) is an emerging therapeutic option for resecting subepithelial lesions (SELs) and epithelial neoplasms. We aimed to systematically review the techniques, applications, outcomes, and complications of EFTR.Methods A systematic literature search was performed using PubMed. All relevant original research articles involving EFTR were included for the review along with case report/series describing novel/rare techniques from 2001 to February 2022.Results After screening 7,739 citations, finally 141 references were included. Non-exposed EFTR has lower probability of peritoneal contamination or tumor seeding compared with exposed EFTR. Among exposed EFTR, tunneled variety is associated with lower risk of peritoneal seeding or contamination compared with non-tunneled approach. Closure techniques involve though the scope (TTS) clips, loop and clips, over the scope clips (OTSC), full thickness resection device (FTRD), and endoscopic suturing/plicating/stapling devices. The indications of EFTR range from esophagus to rectum and include SELs arising from muscularis propria (MP), non-lifting adenoma, recurrent adenoma, and even early gastric cancer (EGC) or superficial colorectal carcinoma. Other indications include difficult locations (involving appendicular orifice or diverticulum) and full thickness biopsy for motility disorders. The main limitation of FTRD is feasibility in smaller lesions (<20–25 mm), which can be circumvented by hybrid EFTR techniques. Oncologic resection with lymphadencetomy for superficial GI malignancy can be accomplished by hybrid natural orifice transluminal endoscopic surgery (NOTES) combining EFTR and NOTES. Bleeding, perforation, appendicitis, enterocolonic fistula, FTRD malfunction, peritoneal tumor seeding, and contamination are among various adverse events. Post OTSC artifacts need to be differentiated from recurrent/residual lesions to avoid re-FTRD/surgery.Conclusion EFTR is safe and effective therapeutic option for SELs, recurrent and non-lifting adenomas, tumors in difficult locations and selected cases of superficial GI carcinoma.
Keywords: endoscopic full thickness resection; full thickness resection device; sub-epithelial lesions; over the scope clips